Dampak Pembangunan Perumahan Terhadap Perubahan Kondisi Lingkungan Di Desa Palasari Kecamatan Legok Kabupaten Tangerang - Wahyu Ramadhan, Wahyu Ramadhan; Moh. Balya Ali Sya'ban (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2024)
Rapid population growth and regional development will affect environmental changes. These changes will inevitably have an impact on human life directly or indirectly, with positive results such as meeting human needs and local and regional economic growth, as well as negative results such as a decrease in environmental quality, the impact analysis method produces data obtained then presented in the form of tables, graphs and then described so as to produce information. The results show that in the period between 2010 - 2022 there has been a growth in housing development which resulted in a reduction in the use of rice fields with an area of 66.6 Ha out of a total of 170.0 Ha. In addition, water sources in the dry season have an impact on the community in the area around the housing after the development, In the analysis of total respondents showed 92% impact on land use, 86% impact on water sources, 59% impact on road conditions, 52% impact on drainage.